Penerapan Model Project Based Learning untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa di Sekolah Dasar - Nisa Aulia (Jurnal Riset Madrasah Ibtidaiyah, 2023)
This research is a Classroom Action Research that aims to improve the creative thinking skills of elementary school students by applying the Project Based Learning learning model. This model is used for the fourth-grade mathematics subject in one of The City Elementary Schools in Jambi through two cycles. The research subjects were 2 teachers and 2 classes totaling 40 students. After the implementation of learning using the Project Based Learning Model in elementary schools, there is an increase in students' creative thinking skills, especially in the fourth-grade elementary school mathematics subjects. The increase can be seen based on the results of the observation of students' creative thinking abilities in the first cycle which increased 15% from the pre-cycle to 65% and in the second cycle the percentage of observations of students' creative thinking abilities increased by 15% from the first cycle to 80%. Likewise, the percentage of student test results in the first cycle 75% increased by 22.5% from the pre-cycle which was only 52.5%. Furthermore, in the second cycle, it increased by 10% to 85%. This percentage shows that there is an increase in students' creative thinking skills in elementary schools by applying the Project Based Learning model. So it can be concluded that the Project Based Learning model can improve the creative thinking skills of fourth-grade elementary school students.